(3eRL GdUhGH HGdeLhf aj Md SdSdI GdeLfhfs - (3GdHhQjfj , GdMSf Hf eMeO Hf eMeO Hf MSf GdUahQj GdHhQjfj, HOQ GdOjf,J (B1024 (3g` s
(3ChdgG (B:s
(3hHYO, aEfg deG JHjf dfG ef bhdg Udi Gddg Ydjg hSde Ef ef GdTYQ dMceg hMce HeG bVGg dg s
(3BNQgG (B:s
(3Hd jLH, Cf jfbWY gfG GdcdGe, hjJYjf Ydi fGXegG, Hd dGWegG, GdSNGe hGddWGe hgPG BNQ GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3hgh TQM GdHhQjfj Ydi GdbUjOI GdeSeGI HGdbQe MTOjI ddehdi MSjf GdTGej GdedbH HbQe MTO EeGe GdLGeY GdCehj HOeTbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B219 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B291s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B470 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3BOGH (B5035) s
Keywords: (3GdCOHs